Beyond viral suppression: decoding the mitochondrial-immune axis in HIV-associated inflammation and immune dysfunction - Okine, Tracy; Hill, Eleanor; Sheran, Kate; Swartz, Talia H. (Frontiers in Cellular and Infection Microbiology, 2025)
Antiretroviral therapy (ART) has transformed HIV into a chronic, manageable condition, yet people living with HIV (PLWH) continue to experience persistent immune activation and systemic inflammation that drive long-term comorbidities, including neurocognitive impairment and cardiovascular disease. This residual inflammation requires new mechanistic explanations and targeted therapeutic approaches. Increasing evidence highlights mitochondria as central hubs in the regulation of cellular metabolism and immune responses. In PLWH, both HIV and ART disrupt mitochondrial function, leading to the release of proinflammatory mediators such as reactive oxygen species (ROS) and oxidized mitochondrial DNA (mtDNA). These signals activate the NLRP3 inflammasome, resulting in secretion of IL-1β and other cytokines. In parallel, excess mitochondrial ATP engages purinergic receptors such as P2X1 and P2X7, propagating inflammatory signaling to surrounding immune cells. This review examines the mito–immune axis in HIV, focusing on OxPhos dysregulation, inflammasome activation, and purinergic receptor signaling, and explores potential interventions—including purinergic antagonists—that aim not only to suppress viral replication but also to restore immunometabolic balance. By recognizing mitochondria as dynamic regulators of immune function, we outline a paradigm shift in HIV treatment that addresses the underlying drivers of chronic inflammation.